Pemberdayaan Komunitas melalui Senam Sehat bagi Lansia dan Perempuan Usia Produktif: Pengabdian - Eli Retnowati; Ariadi Setiawan; Novana Resi Famelia; Achmad Hayden Syafaat Putra (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Physical health, particularly among the productive age group and the elderly, is an essential aspect of achieving an optimal quality of life. One of the simplest strategies to maintain and improve health is engaging in regular physical activities, such as healthy gymnastics. This community service program aimed to implement a weekly healthy gymnastics activity to improve physical endurance, body fitness, and public awareness regarding the importance of adopting a healthy lifestyle. The program was carried out through mentoring and empowerment methods, which included brief health education sessions on the benefits of exercise, hydration, and balanced nutrition, followed by collective healthy gymnastics practice. The results indicated a high level of enthusiasm from participants, as reflected in their consistent weekly attendance and active participation throughout the activity. Moreover, participants reported improvements in their physical condition, greater motivation to exercise, and stronger awareness of the importance of maintaining physical health. Therefore, this program has the potential to become a sustainable community-based initiative that supports the improvement of the quality of life in Pagesangan Subdistrict.